2017
DOI: 10.1080/09168451.2017.1379351
|View full text |Cite
|
Sign up to set email alerts
|

Induction of plant disease resistance upon treatment with yeast cell wall extract

Abstract: It has been reported that treatment with yeast cell wall extract (YCWE) induces PDF1 and PR-1 gene expression; these transcripts are important markers of plant disease resistance, though the detailed signaling mechanisms that induce these defense responses are still unknown. In this report, we found that YCWE treatment triggered rice cell suspension cultures to accumulate phenylalanine (Phe), cis-12-oxo-phytodienoic acid (OPDA), 12-hydroxyjasmonoyle isoleucine (12OHJA-Ile), and azelaic acid (AzA). YCWE treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In addition to PR gene activation, a yeast cell wall extract added to rice cell suspension culture induced accumulation of signaling molecules involved in SAR; azelaic acid (AzA) and phenylalanine (Phe), as well as the wound-based signaling compound JA, and related jasmonate intermediates and actives 12-hydroxyjasmonoyl isoleucine and 12-oxo-phytodienoic acid (Yaguchi et al, 2017). These compounds were proposed to prime against the necrotrophic pathogen Botrytis cinerea in Arabidopsis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to PR gene activation, a yeast cell wall extract added to rice cell suspension culture induced accumulation of signaling molecules involved in SAR; azelaic acid (AzA) and phenylalanine (Phe), as well as the wound-based signaling compound JA, and related jasmonate intermediates and actives 12-hydroxyjasmonoyl isoleucine and 12-oxo-phytodienoic acid (Yaguchi et al, 2017). These compounds were proposed to prime against the necrotrophic pathogen Botrytis cinerea in Arabidopsis .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have been performed to test the efficacy of microbial fermentation products (MFPs) as elicitors of plant defence, including a yeast cell wall extract derived from the beer brewing process (Yaguchi et al, 2017), and a compound derived from glutamate fermentation (Chen et al, 2014). Derivatives of the yeast cell wall, including glucan, mannon, and chitin, have all been investigated as inducers of plant defence (Reglinski et al, 1994; Boller, 1995; Reglinski et al, 1995; Minami et al, 2011; Narusaka et al, 2015; Yaguchi et al, 2017), whereas lactic acid bacteria have been shown to prevent fungal disease in the field (Oliveira et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Plant pattern-recognition receptors that perceive yeast PAMPs remain largely unknown, although many studies demonstrate the ability of yeasts to activate plant immune signaling. For example, yeast cell wall extract of the budding yeast Saccharomyces pastorianus activates JA and azelaic acid signaling to induce plant disease resistance (Yaguchi et al, 2017). In Arabidopsis, yeast cell wall extract activates the JA, ethylene, and SA signaling pathways, and SA accumulation and signaling were required for induced resistance (Narusaka et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several plants exhibit multiple responses to various yeast elicitor preparations; such as autoclaved baker's yeast (Saccharomyces cerevisiae), preparations from S. cerevisiae cell walls, or commercial yeast extract. These responses include, increased immunity against pathogens, induction of reactive oxygen species accumulation, and activation of known immune signaling pathways, in the model plant Arabidopsis thaliana (referred to hereafter as Arabidopsis; Raacke et al, 2006;Khokon et al, 2010;Minami et al, 2011;Ye et al, 2013;Narusaka et al, 2015;Yaguchi et al, 2017) and other plants (Sun et al, 2018a(Sun et al, , 2018b. Raacke et al (2006) used reverse genetics with Arabidopsis to demonstrate that yeast treatments induced salicylic acid (SA) dependent immunity against Pseudomonas syringae; however, induced resistance against the fungal pathogen Botrytis cinerea (hereafter referred to as Botrytis) was independent of the SA, jasmonate, and camalexin pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The increase of intermediate, precursors and catalytic enzymes involved in jasmonic acid biosynthetic pathways were reportedly observed following yeast extract elicitation (Yaguchi T et al, 2017;Hasanloo T et al, 2009). Thus, chitosan and yeast extract would bi-laterally enhance the aloe-emodin production through the jasmonic acid-signalling pathway and create a new synergistic elicitor duo.…”
Section: Simultaneous Double Elicitation On Aloe-emodin Productionmentioning
confidence: 96%